STRATEGI PENGEMBANGAN MUARA SUNGAI YEH MATAN SEBAGAI OBJEK WISATA AIR DI DESA TEGAL MENGKEB KECAMATAN SELEMADEG TIMUR KABUPATEN TABANAN - Anak Agung Putu Agung (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractOne of the development in tourism industry can be done by develop the tourist destinationas a tourist attraction. Development of tourist attraction is certainly planned andimplemented in accordance with the potential and capabilities of the region. One ofalternative to develop the tourist attraction and able to be selected as the tourist destinationespecially in Tegal Mengkeb village is water attraction at estuary of Yeh Matan river whichrelated to nature tourism.The used method in this study is a combination between qualitative and quantitative researchmethod, data collection techniques by questionnaires, interviews, literature study anddocumentation. Data analysis techniques using SWOT analysis to determine the internaland external factors position in development of yeh matan estuary as water attraction.The results of research according to SWOT analysis obtained the average value for internalfactor is 3,057 and external factor is 3,024. It means that the estuary of Yeh Matan river arein a favorable position, maintain and control, maintain the condition of internal factor thathave existed without make changes as water attraction.Require the cooperation and integrated partnership among community, village officials,Government of Tabanan Regency and related stakeholders to promote the estuary of YehMatan river as water attraction at Tegal Mengkeb village, East Selemadeg Sub District,Tabanan Regency.